Удосконалення організаційного механізму державних капітальних вкладень - Шут, С. О. (Ways to Improve Construction Efficiency, 2013)
The organizational weaknesses of planning and management of state capital investments in construction are analyzed, an ordered interaction scheme of public authorities at central, regional and local levels is proposed.